Republic of India : Piloting and Operationalization of City Sanitation Plans towards Outcome Oriented Sector Investments - World Bank (Washington, DC, 2015)
This synthesis report details the process, outputs and intermediate outcomes of the World Bank’s Water and Sanitation Program (WSP) Technical Assistance (TA) to pilot and operationalize city sanitation plans (CSPs) towards outcome oriented sector investments (P131967). This TA addresses issues of ad hoc planning though CSPs that are holistic, intended for city-wide implementation and address the full cycle of sanitation. However, prior to preparation and operationalization of CSPs, it was recognized that this needed to be anchored in a statewide sanitation program. The statewide sanitation program needed to: estimate and provide for the capital requirements to address the gaps in sanitation infrastructure across the sanitation service delivery chain (collection, treatment and disposal), estimate the operation and maintenance (OM) requirements, and set out the framework for prioritization of cities, and attendant institutional frameworks. This TA aimed at piloting and operationalization of CSPs towards outcome oriented sector investments, by supporting (i) select state and local governments with technical assistance to operationalize city sanitation plans by targeting outcome oriented investments, and (ii) improving the institutional and regulatory framework and strengthening state and local government capacity for efficient and sustainable delivery of Government of India or World Bank or other development partner funded programs.